2013
DOI: 10.5194/os-9-1003-2013
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure measurements and estimates of entrainment in the Denmark Strait overflow plume

Abstract: Abstract. To examine processes controlling the entrainment of ambient water into the Denmark Strait overflow (DSO) plume / gravity current, measurements of turbulent dissipation rate were carried out by a quasi-free-falling (tethered) microstructure profiler (MSP). The MSP was specifically designed to collect data on dissipation-scale turbulence and fine thermohaline stratification in an ocean layer located as deep as 3500 m. The task was to perform microstructure measurements in the DSO plume in the lower 300… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 37 publications
(56 reference statements)
7
33
1
1
Order By: Relevance
“…This hypothesis was supported by microstructure measurements by Paka et al . [], who concluded that vertical turbulent mixing is not the major process controlling entrainment in the DSOW plume at ∼200 km from the sill. Detailed process studies on the entrainment in the region close to the sill of Denmark Strait are lacking; it is therefore still unclear which process dominates the entrainment in this specific region.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was supported by microstructure measurements by Paka et al . [], who concluded that vertical turbulent mixing is not the major process controlling entrainment in the DSOW plume at ∼200 km from the sill. Detailed process studies on the entrainment in the region close to the sill of Denmark Strait are lacking; it is therefore still unclear which process dominates the entrainment in this specific region.…”
Section: Introductionmentioning
confidence: 99%
“…The data measured along AUV leg 7 were taken for the upper integration limit. To our minds, the main source of errors of the calculated entrainment rates lies in linear vertical interpolation between the measured dissipation rates, because the vertical profiles of ε are known to be highly variable (patchy) due to turbulence intermittency [e.g., Paka et al ., ]. For this reason, it is hardly expected that the accuracy of the w e estimates is better than one order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…Second, based on measurements of dissipation of turbulent kinetic energy (hereafter simply referred to as dissipation) in the DSO plume at 200 km downstream of the sill, Paka et al . [] computed much smaller entrainment rates than required to explain the rapid warming of the plume observed by Voet and Quadfasel []. Paka et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the methods outlined in previous overflow plume studies (e.g., Arneborg et al, 2007;Paka et al, 2013;Zhurbas et al, 2016), the integrated entrainment rate (w layer ) was calculated as:…”
Section: Data Set Sources and Processingmentioning
confidence: 99%